Systematic Review: Risk Factor Analysis for Malaria Incidence in Indonesia - Dwi Kuntari, Ayu; Rahardjo, Mursid; Setiani, Onny (Rifa'Institute, 2025)
Malaria remains one of the public health issues in Indonesia, caused by the mosquito vector Anopheles spp., with a fairly high morbidity and mortality rate and a strong potential to trigger extraordinary events (outbreaks) in Indonesia. One of the ways to control malaria is by controlling the risk factors. The control of risk factors will be successful if its implementation is based on accurate data and information about the vector, the environment, its breeding, as well as the behaviour of the local community. The aim of this study is to analyse the risk factors for malaria incidence in Indonesia. Method: This study used a systematic review of five journal articles on malaria incidence in Indonesia, each using a case-control research method. Results: Based on the similarity of variables between researchers, there are several statistically significant risk factors, namely the use of wire mesh on ventilation, using mosquito nets, tight wall conditions, the presence of breeding places, the presence of resting places and being outside the house at night. Meanwhile, the protective factor for malaria incidence in Indonesia based on the average Odds Ratio (OR) above was the presence of breeding sites (properly managed). Conclusion: There are thirteen variables that become risk factors and one protective factor of malaria, namely the presence of breeding sites